"Manning the barricades" : managing organisational boundaries for effective e-learning - Rossiter, D. (Cranfield University, 2009)
This paper explores how the boundaries within organisations, structural and cultural, impact the take-up of an innovation, such as e-learning in a complex higher education and defence environment. In doing so, the paper examines how structure and environment act as impediments, or facilitators, to newer education and training developments and whether these factors can be mitigated against or managed. The most apparent barriers are structural. These are sanctioned forms that delineate organisational workgroups and entities. They are inextricably meshed with the policies, processes and practices that scaffold teaching and learning activity. Structural dimensions can generally be managed or guided towards a common mission, goal or endpoint. The more pervasive elements, however, are cultural and include issues pertaining to role and identity and working within a more ambiguous environment. Many human factors associated with change may be observed as overt behaviour, but often they emerge as more subtle manifestations, which are both difficult to identify and to manage in organisational settings. Strategies that rely on influence, rather than control, can be more appropriate in the latter case. The most challenging issues often occur at the boundaries of a system. Commonly these complex issues and behaviours are interpreted as problems, and much of the organisational effort is directed towards overcoming such change barriers. This paper will examine various aspects of boundary behaviour, drawing on theories and models of change, as well providing practical examples and strategies to manage these boundary transitions more effectively.
presented at Defence Academies & Colleges International e-Learning Conference, 25th – 27th March 2009, Stellenbosch, South Africa.
Keywords: organisational change; e-learning; complex adaptive systems